Botswana : 2007 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Botswana. (IMF Staff Country Reports; Country Report ;, 2008)
Sound macroeconomic policies, good governance, and high levels of investment, supported by diamond and other mineral production, have moved Botswana into the ranks of middle-income countries. Maintaining fiscal surpluses over the medium term is essential to accumulate savings for the period when diamond revenues decline. Striking an appropriate balance between monetary and exchange rate policy objectives is critical. The banking sector is sound and near-term risks are well contained, but there is scope for financial sector reform. Continued structural reform and improvements in statistics are essential.